Measuring community urbanicity and its influence on household food security across Nepal’s agroecological zones - Graham, Elizabeth; Thorne-Lyman, Andrew L.; McGready, John; Mui, Yeeli; Manohar, Swetha; Neupane, Sumanta; Fanzo, Jessica; West, Keith P., Jr. (Elsevier, 2024)
Background Urbanization influences food systems and food security, but research on these associations in low- and middle-income countries remain limited, partly because of the binary and unstandardized “urban compared with rural” classifications.